Efektivitas Pelatihan Bantuan Hidup Dasar (Bhd) Terhadap Kompetensi Perawat Non-IGD Dalam Menangani Henti Jantung - Mebri, Elysabeth; Ramli, Rachmat; Tondok, Santalia Banne; Asrianto, Asrianto; Abdullah, Rusli (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Cardiac arrest is an emergency that requires rapid and appropriate treatment. Basic Life Support (BLS) training is an important effort to improve the competence of healthcare workers in providing first aid in this situation. However, nurses working outside the emergency department (non-ER) often do not receive routine training, thus hampering the potential for an effective initial response. Objective: To determine the effectiveness of BLS training on improving the competence of non-ER nurses in managing cardiac arrest. Methods: This study used a quasi-experimental design with a pretest-posttest approach without a control group. The subjects were 40 non-ER nurses at a government hospital who participated in BLS training. Data were collected using a questionnaire and a skills observation checklist, analyzed using the Wilcoxon test. Results: There was a significant increase in cognitive and psychomotor competency scores after BHD training (p < 0.001). The average pretest score was 58.3, increasing to 83.7 on the posttest. Conclusion: BHD training effectively improved the competency of non-ED nurses in managing cardiac arrest, both in terms of knowledge and skills. Routine training should be included in hospital quality improvement programs.